A HL7 transformer application for vaccination data report. (30th January 2006) - Lin, I-Chun; Hsu, Hui-Mei; Liu, Chien-Tsai
In this paper, we design a data transformer to transform Comma Separated Value (CSV) format into Health Level Seven (HL7) messages without losing syntax and semantics. The algorithm of the data transformer is similar to a generic parser for solving scheme-level mapping problems. It can be extended to transform non-uniform formats for exchanges among different hospital information systems. To show the flexibility and scalability of the algorithm, we use it for the transformation of reported data in the Vaccination Reporting System (VRS). Through the data transformer, different formats of vaccination data can be reported directly to the Taiwan's Center for Disease Control.